2017
DOI: 10.1007/s11325-017-1464-y
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of circulating microvesicles is associated with the severity of obstructive sleep apnoea

Abstract: The relationship between the diurnal variability of CD41+ MVs and disease severity as well as the effect of CPAP treatment on MV levels support the role of MVs in the pathophysiology of OSA. More importantly, considering the significant diurnal variation in circulating MV levels, introduction of strict protocols for blood sampling is required for MV measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Disrupted sleep is a major component in the pathophysiology of OSA. Still, the number of studies investigating inflammatory biomarkers before and after night is low (Bikov et al., ; Jordan et al., ; Kunos et al., ; Mills, Natarajan, Von Kanel, Ancoli‐Israel, & Dimsdale, ; Nobili et al., ). In contrast to the findings on CRP (Mills et al., ), we did not find an overnight change in C3a or SC5b‐9 in the OSA or control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disrupted sleep is a major component in the pathophysiology of OSA. Still, the number of studies investigating inflammatory biomarkers before and after night is low (Bikov et al., ; Jordan et al., ; Kunos et al., ; Mills, Natarajan, Von Kanel, Ancoli‐Israel, & Dimsdale, ; Nobili et al., ). In contrast to the findings on CRP (Mills et al., ), we did not find an overnight change in C3a or SC5b‐9 in the OSA or control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Polysomnography was performed as it was described previously (Bikov et al., ; Kunos et al., , ) using Somnoscreen Plus Tele PSG (Somnomedics GmbH Germany). Electroencephalogram, electrooculogram and electromyogram, thoracic and abdominal respiratory excursions, breath sounds, nasal airflow, electrocardiogram and oxygen saturation were recorded according to guidelines (Kushida et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…These, together with hypoxia itself induce the expression of adhesion molecules, such as P-selectin. P-selectin is expressed upon stimulation by thrombin [3], hypoxia [4] or cytokines [5] by platelets and endothelial cells, however platelet P-selectin expression may be less important in OSA compared to endothelial P-selectin [6,7]. P-selectin enhances the adhesion between leukocytes and endothelial cells thus slowing down the rolling of leukocytes and facilitating their extravasation.…”
Section: Introductionmentioning
confidence: 99%
“…P-selectin enhances the adhesion between leukocytes and endothelial cells thus slowing down the rolling of leukocytes and facilitating their extravasation. P-selectin has extensively been investigated in OSA [6][7][8][9][10][11][12] with some studies reporting elevated blood P-selectin levels [8,11,12], but not all [6,7,10]. A potential explanation for the contradictory findings could be the presence of comorbid obesity, as one study reported no difference in circulating P-selectin levels between OSA and body mass index (BMI)-matched controls [6].…”
Section: Introductionmentioning
confidence: 99%
“…Annexin V has been associated with endothelial dysfunction and is a predictor of cardiac events [76]. Endothelial dysfunction and increased serum levels of annexin V have been observed in OSA patients, and is exacerbated during sleep [77][78][79]. Annexin V is associated with increased prevalence of atrial natriuretic peptide granules and has been shown to concentrate around the Z-line in rat atria [80,81].…”
Section: Resultsmentioning
confidence: 99%